Evaluación de la caracterización florística de especies maderables y no maderables y su contribución al ambiente en un sector del barranco vicente najar - Huamán Ampuero, Roxana (2015)
With the intention of identifying to the providing useful wood and not providing useful wood species by means of its characterization flora and its contribution to the environment of the Vicente Najar ravine, biometrics is the calculation of the individuals found in 7912.5 m2 approximately. Was assessed 69 trees for tree species, contained in six sample units to which meas u red the DBH (Diameter at breast height) to the species with 1 O cm to more. The extent of the DBH mínimum recorded was 1 Ocm and the maximum 78 cm. From the information obtained in the biometric phase there was obtained that, the species with a major lndex of value of importance were Cecropea sp. "The cetico ", Mangifera sp. "Handle", Amazonian Aniba "moena white ". They were achieved to identify for the providing useful wood species 19 families and 27 species and for the not providing useful wood species 11 families and 14 were identified, both identifications were realized to level of scientific and common name. To determine the characterization of the floristic species both timber and nontimber can be seen that contribute to the environment as a regulator of the microclimate that sorne species possess a considerable height and also serve as shelter of great diversity, has a potential value of the environmental landscape with a better and proper management within the area. Key words: Floristic characterization, contribution to the environment, importance value index